Effects of tai chi on inhibitory function in college students evidence from heart rate variability - Hou, Jinmei; Yin, Hengchan; Cui, Lei; Shen, Qiqi; Xia, Tong; Zhang, Jingyi (The Journal of the International Society of Chinese Health Practices, 2024)
See PDF for details